PREFERENSI PERANCANGAN KONSEP HOME ZONE DAN HOME RANGE SEBAGAI RESILIENSI MASA PANDEMI - Indarto; Ahmad Fajar Ariyanto (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2022)
Abstract The purpose of this study was to determine the application of the concept of Home Zone and Home Range in simple residential interiors, especially the arrangement of furniture layouts related to social distancing and circulation. The data collection method is in the form of deepening related literature and field documentation of related objects as well as interviews with related resource persons. Data analysis refers to an interactive analysis model combined with a pre-design alternative model which includes three components, namely: data reduction, data display (displaydata) and data validation (verification). The results of the study indicate that a good residential design must start from a well-planned surrounding environment and well-planned interior design, including meeting health and safety standards as a Healthy Home that fulfills physiological and psychological functions. The results of this study are expected to be an evaluation material for relevant stakeholders in the fulfillment of development facilities in the future.